THE LEXEME “SUN” AS AN ELEMENT OF THE FIGURATIVE SYSTEM OF WORKS BY M. A. SHOLOKHOV - Nurullina, Guzel; Latfullina, Landysh; Usmanova, Liliya (Revista Inclusiones, 2019)
The problems of compatibility of a word and its associative opportunities in a space of a figurative discourse are considered in the article, the author's priorities in a figurative comprehension of a lexeme “sun” in the works by M. A. Sholokhov are identified and its lexical and semantic compatibility both at the level of binary connections, and within an expanded context is characterized. The analyzed ways of verbalization of the author's meanings at the level of contact and distant communications allowed to reveal cognitive, mental and emotive spheres of consciousness of the poet and also to interpret a phenomenon of the Universum of M.A. Sholokhov as the difficult phenomenon defining his uniqueness and originality in the Russian literature. It is noted that the text realization of words in the conditions of a figurative discourse leads to the integration of various aspects of reality and recreates the author's perception of the world based on the indissoluble, interpenetrating unity of objective and subjective, logical and sensual, rational and emotional.